The Preparative Nonreflux Procedure on Disproportionation Reaction in Small-Scale Synthesis - Rohmawati, Dini; Handayani, Sri; Budimarwanti, Cornelia; Sari, Dista Arum; Yuliyanti, Diana; Abdillah, Muchammad Ikmal; Pratiwi, Oktavia; Anasriah, Tria Novita (Indonesian Journal of Chemistry and Environment, 2024)
Reactions with nonreflux procedures are based on the mechanical impact energy to promote the transformation process of chemicals. The simple procedures are grinding-milling, microwave-assisted, and ultrasonic-assisted. Generally, the procedures were undergoing nonsolvent or solventless reaction conditions also in effective and efficient processes, which corresponds to the principles of green chemistry. In its development, disproportionation reaction could also be undergone by applying these methods. This article discussed the preparative procedures of nonreflux with grinding, shaking, ultrasonic-assisted, and microwave-assisted in disproportionation reactions, which later could be used as standard procedures according to green chemistry and sustainable development goals (SDGs).